Penggunaan Game-Based Learning Dalam Meningkatkan Kemampuan Berbicara Siswa Di Mata Pelajaran Bahasa Indonesia - Alysa Rahma Wulan; Elsa Resta Pania; Ichsan Fauzi Rachman (Publikasi Inspirasi Indonesia, 2025)
The use of Game-Based Learning (GBL) in Indonesian language instruction, particularly in enhancing students' speaking skills, represents an innovation aligned with the needs of 21st-century learners who tend to favor visual, interactive, and challenge-based activities. The purpose of this study is to explore the implementation of the Game-Based Learning method in Indonesian language teaching to improve students’ speaking abilities, identify the types of games used in GBL and their impact on students' speaking skills, and to determine the supporting and inhibiting factors in the implementation of Game-Based Learning in enhancing speaking skills in Indonesian language lessons. This study employs a qualitative research method. The findings reveal that the implementation of GBL also faces challenges such as limited facilities, lack of teacher training, varying student characteristics, and time constraints.